As relações entre propriedade, gestão e família e a adoção de práticas de governança corporativa em empresas familiares: Um Estudo de Caso Múltiplo no Rio Grande do Sul - Girardi, Henrique Ullmann (Universidade do Vale do Rio dos Sinos, 2019)
This work aims to investigate the relationship between ownership, management and family structure and the adoption of corporate governance practices in three family companies. The structure of property, management, and family is presented through the three-circle model of Tagiuri and Davis (1996) and the three-dimensional model of Gersick et al (1997). Corporate governance practices follow the recommendations of the Brazilian Institute of Corporate Governance (IBGC, 2016), which is today one of the great references for the subject in Brazil. The methodology chosen was the multiple case studies, because it is possible to identify different configurations of property, management, and family structure, and to study the different realities. Each case is presented and analyzed initially in isolation and then with the triangulation of the cases, with interviews, questionnaire application, and document collection. The interviews were conducted with representatives of the ownership, management, and family of each of the companies. With the information obtained in the data collection phase, it is possible to identify relations between the structure of ownership, management, and family and the adoption of corporate governance practices in the three studied companies. In company “A”, we identify relations between the concentration of ownership and centralized management and low level of corporate governance, including low governance development in the family circle. In company “O”, it is possible to relate the corporate governance practices that are currently under development, with the relevance of the controlling family and succession planning, which has begun to be discussed recently among family owners. And finally, in company “E”, corporate governance practices are related to the recent entry of a new external partner to the family, which changed the company's structure and the active participation of the founder.
Keywords: Empresa familiar; Governança Corporativa; Teoria da agência; Modelo dos três círculos; Family business; Corporate Governance; Agency Theory; Three-Circle Model; ACCNPQ::Ciências Sociais Aplicadas::Administração